Comparison of Three International Charts Used to Monitor Gestational Weight Gain: Results from a Brazilian Multiple Cohort Dataset (P11-128-19). (13th June 2019) - Farias, Dayana; Carrilho, Thais; Alves, Ronaldo; Costa, Nathalia; Batalha, Monica; Aguiar, Emanuelli; Gonzalez, Mylena; Kac, Gilberto; Consortium, Brazilian Gestational Weight Gain; Domingues, Marlos; Drehmer, Michele; Granado, Silvana; et al.
Abstract: Objectives: To compare gestational weight gain (GWG) trajectories of Brazilian women with three international charts used to monitor GWG, and to test whether there are differences in the classification of total GWG centiles between these charts. Methods: This is a multiple combined cohort dataset with data from 10 Brazilian studies with repeated measures (mean of 6.9 measures) of GWG. Total GWG was obtained by the difference between the weight measured up to 14 days before delivery and the weight measured in the 1st trimester [Intergrowth-21st, I-chart] or the pre-pregnancy self-reported weight [Life-cycle project, L-charts; and Hutcheon, H-charts]. A total of 3, 423 (23, 340 observations) adult women with singleton pregnancies and free of hypertension and diabetes were included. We compared graphically the mean linear prediction (linear mixed-effect models) of Brazilian women GWG with the 50th centile of three international charts. The agreement of total GWG classification in < 10th, 10th–90th and > 90th centiles was tested using Cohen's kappa coefficient according to Landis & Koch classification. Results: Women had a mean total GWG of 12.2 kg (SD: 5.8) and were, on average, 27.4 (SD: 5.8) years old. Pre-pregnancy normal weight women had a different pattern of GWG compared to I-chart, and the mean GWG of this group was slightly higher than the 50 th centile of the L-chart. Underweight and obese women presented a different slope of GWG compared with the 50 th centiles of H and L-charts. Pre-pregnancy overweight women presented a linear prediction that overlaps the 50 th centile of the L-chart in the second half of pregnancy (Figure ). It was observed a moderate agreement (kappa = 0.56) comparing the 10 th, 10 th –90 th and 90 th centiles classification between L and I-charts for normal weight women. L and H-charts presented a substantial agreement for underweight (kappa = 0.71), and moderate for overweight (kappa = 0.52) and obese women (kappa = 0.59). Conclusions: L-charts are the ones that most closely resemble the Brazilian GWG distribution, especially for overweight women. We observed moderate agreement in the GWG classification of women in the 10 th and 90 th centiles between charts, which may lead to different diagnosis of GWG depending on which chart is used. This is a first step to create new Brazilian GWG recommendations. Funding Sources: The Brazilian National Council for Scientific and Technological Development and Bill and Melinda Gates Foundation (Grand Challenges Exploration). Supporting Tables, Images and/or Graphs: